2011
DOI: 10.1021/ic2003723
|View full text |Cite
|
Sign up to set email alerts
|

Emissive Iridium(III) Diimine Complexes Formed by Double Cyclometalation of Coordinated Triphenylphosphite

Abstract: We report on the synthesis of a new series of iridium(III) complexes functionalized with various diimine chromophores, together with a facially coordinated dicyclometalated phosphite chelate and a monodentate anionic ancillary. This conceptual design presents a novel strategy in obtaining a new class of iridium(III) diimine complexes without employment of traditional nitrogen-containing polyaromatic cyclometalates. Additionally, we discuss the basic charactersistics of the ground and lower-lying excited states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…[Ir(dpyx)(dfppy)Cl] (Scheme 2). By contrast, Chi and co-workers 25,26 and Guerchais and Zysman-Colman 27 have independently reported the isolation of a class of Ir(III) complexes with chelates arranged in a distinctive 3 + 2 + 1 mode, for example, complexes A and B, where the "nonplanar" tridentate chelate adopts a distinctive facial geometry. With this success in changing chelate from bidentate to tridentate and altering their bonding from meridional to facial coordination, it is clear that preparation of Ir(III) complexes bearing tetradentate chelate in either planar or nonplanar geometries should be also accessible.…”
Section: ■ Introductionmentioning
confidence: 98%
“…[Ir(dpyx)(dfppy)Cl] (Scheme 2). By contrast, Chi and co-workers 25,26 and Guerchais and Zysman-Colman 27 have independently reported the isolation of a class of Ir(III) complexes with chelates arranged in a distinctive 3 + 2 + 1 mode, for example, complexes A and B, where the "nonplanar" tridentate chelate adopts a distinctive facial geometry. With this success in changing chelate from bidentate to tridentate and altering their bonding from meridional to facial coordination, it is clear that preparation of Ir(III) complexes bearing tetradentate chelate in either planar or nonplanar geometries should be also accessible.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Recently, in sharp contrast to the triphenyl phosphite that yields double cyclometalation, , a bulky phosphine ligand such as PPh 3 , was found to react readily with the aforementioned Ir(III) source complex [Ir(tht) 3 Cl 3 ], giving two isolable products, namely [Ir(tht) 2 (PPh 3 )Cl 3 ] ( 5 ) and [Ir(tht)(PPh 3 ) 2 Cl 3 ] ( 6 ), in a stepwise fashion (Scheme ). The monosubstitution product 5 was obtained as the major product for the reaction using a stoichiometric amount of PPh 3 , while the disubstitution product 6 was isolated by addition of 2 equiv of PPh 3 to [Ir(tht) 3 Cl 3 ] or by treatment of the monosubstitution product 5 with a another 1 equiv of PPh 3 under similar conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that treatment of [IrCl 3 (tht) 3 ] (tht = tetrahydrothiophene) with an equimolar amount of triphenylphosphite (tpitH 2 ) and diimine, such as 2,2′-bipyridine and 2,2′-biquinoline, gave formation of novel diimine complexes A and B (see below) in high yields . The added diimine and phosphite would easily replace all three tht ligands and then formed certain unknown intermediate initially.…”
Section: Resultsmentioning
confidence: 99%